Tradisi Ritual Kematian Islam Kejawen Ditinjau Dari Sosiologi Hukum Islam - Mahmudah, Nurul; Saputera, Abdur Rahman Adi (Universitas Islam Negeri Raden Intan Lampung, 2019)
The arrival of Islam on Java gave a new color to the ceremonies in the Javanese tradition, including the death ceremony. Although it is now